Fuel Production from LDPE-based Plastic Waste over Chromium Supported on Sulfated Zirconia - Latifah Hauli; Karna Wijaya; Akhmad Syoufian (Indonesian Journal of Chemistry, 2020)
The preparation, characterization, and catalytic activity test of sulfated zirconia (SZ) modified with chromium for the hydrocracking of LDPE-based plastic waste have been investigated. SZ was prepared by wet impregnation method using zirconia nanopowder (ZrO2) and H2SO4 solution. SZ was further modified with chromium (0.5, 1.0, and 1.5% wt.%) by refluxing in aqueous solution of Cr(NO3)3·9H2O, followed by calcination and reduction processes. The prepared catalysts were characterized by SEM-Mapping and TEM. Hydrocracking of LDPE-based plastic waste was conducted at various temperatures and various catalysts. In addition, the optimum catalyst was repeatedly used for the reaction to demonstrate the stability of the catalyst. Liquid products obtained by hydrocracking were characterized by GCMS. The results showed that the morphology of the prepared catalysts had different sizes and disordered shapes after the addition of sulfate and Cr. The effective temperature for hydrocracking was 250 °C. The highest selectivity to liquid product and gasoline fraction were 40.99 and 93.42 wt.%, respectively, and were obtained over Cr/SZ with 1.0 wt.% Cr. Hydrocracking of plastic waste over the used Cr/SZ catalyst with 1.0 wt.% Cr showed that the Cr/SZ catalyst was stable and reusable up to three repetitions.